ANALYSIS OF VITAMINS IN THE ROOTS AND STEMES OF THE PLANT RUBUS CESIUS L (Scientific journal of the Fergana State University, 2025)
The article describes methods for determining the amount of vitamins in the above-ground and underground parts of the plant Rubus caesius L. (blackberry), grown in the Fergana region, Fergana region in winter. The results obtained are presented in the form of tables and diagrams. High performance liquid chromatography was used to determine the amount of vitamins.